Belief Strength in Low-Priced Product Consumption Experience - Ignasius Heri Satrya Wangsa (Jurnal Manajemen dan Bisnis Indonesia, 2013)
This research aims to identify emotional values within low-priced product attractiveness context by employing scientific rationalization on belief strength in consumption experience. Comparison among two price-benefit regimes i.e. â€œcheap is the bestâ€ and â€œexpensive is the bestâ€ is made. Belief strength is applied to explore new dimension in low-priced product consumption experience research. Keywords: belief strength, low-priced product attractiveness, low-priced product consumption experience